2017
DOI: 10.1002/pssb.201700380
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanical Properties of Graphyne, Graphdiyne, and Other Poly(Phenylacetylene) Networks

Abstract: We simulate, analyse and compare the mechanical properties of a number of molecular sheet‐like systems based on fully substituted, penta‐substituted, tetra‐substituted and tri‐substituted poly(phenylacetylene) using static force‐field based methods. The networks are modeled in a 3D environment with and without inter‐layer interactions in analogy to graphite and graphene respectively. It is shown that by varying the type of substitution and the length of the acetylene chain, one may control the mechanical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…The theoretical paper presented by the Malta group, 'On the compressibility properties of the wine-rack-like carbon allotropes and related poly(phenylacetylene) systems' [15] looks at a number of carbon-based two-dimensional nano networks, some of which are shown to exhibit more than one negative mechanical property. This work, which extends earlier studies of the same authors, [16,17] shows how some of the networks can be both auxetic and exhibit negative linear compressibility.…”
supporting
confidence: 87%
“…The theoretical paper presented by the Malta group, 'On the compressibility properties of the wine-rack-like carbon allotropes and related poly(phenylacetylene) systems' [15] looks at a number of carbon-based two-dimensional nano networks, some of which are shown to exhibit more than one negative mechanical property. This work, which extends earlier studies of the same authors, [16,17] shows how some of the networks can be both auxetic and exhibit negative linear compressibility.…”
supporting
confidence: 87%
“…This led to various studies in the last decades which were focused on the design and investigation of honeycombs specifically engineered to exhibit anomalous or superior thermomechanical properties, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] such as a negative Poisson's ratio (auxetic behavior). [8][9][10][11][12][13][14][15] Given the advantages of honeycombs over nonporous solids, [6,7,16,17] when put in the context of the developments which are being made on "negative thermomechanical properties," it is not surprising that research in the field of "negative honeycombs" is still the subject of extensive research. [3,4,9,11,17,30,31,[51][52][53][54][55] Previous studies [12,30,31,51,52] have shown some special characteristics of centrosymmetric honeycombs with T-shaped joints.…”
Section: Introductionmentioning
confidence: 99%
“…It is due to these enhanced properties and the wide range of applications that in recent years, there have been various studies which have attempted to design, model, synthesize, manufacture, or characterize materials and metamaterials which exhibit one or more of these anomalous properties. These include zeolites [11][12][13][14], silicates and other minerals [15], and polymeric systems [2,[16][17][18][19][20][21][22] which exhibit negative Poisson's ratios, in addition to metal organic frameworks (MOF) which exhibit negative linear compressibility [23][24][25]. In tandem, there has also been a significant amount of research aimed at exploring new mechanisms leading to anomalous behaviors.…”
Section: Introductionmentioning
confidence: 99%